Profound and selective lymphopaenia in primary lymphatic anomaly patients demonstrates the significance of lymphatic-lymphocyte interactions - Pearce, Julian; Hadcocks, Linda; Mansour, Sahar; van Zanten, Malou; Jeffery, Steve; Gordon, Kristiana; Ostergaard, Pia; Mortimer, Peter; Macallan, Derek C. (Frontiers in Immunology, 2023)
Introduction The lymphatic system has a pivotal role in immune homeostasis. To better understand this, we investigated the impact of Primary Lymphatic Anomalies (PLA) on lymphocyte numbers and phenotype. Methods The study comprised (i) a retrospective cohort: 177 PLA subjects from the National Primary Lymphatic Anomaly Register with clinical and laboratory data, and (ii) a prospective cohort: 28 patients with PLA and 20 healthy controls. Patients were subdivided using established phenotypic diagnostic categories and grouped into simplex (localised tissue involvement only) and systemic (involvement of central lymphatics). Further grouping variables included genital involvement and the likelihood of co-existent intestinal lymphangiectasia. Haematology laboratory parameters were analysed in both cohorts. In the prospective cohort, prospective blood samples were analysed by flow cytometry for markers of proliferation, differentiation, activation, skin-homing, and for regulatory (CD4+Foxp3+) CD4+ T cells (Treg). Results In patients with PLA, lymphopaenia was frequent (22% of subjects), affected primarily the CD4+ T cell subset, and was more severe in subjects with systemic versus simplex patterns of disease (36% vs 9% for lymphopaenia; 70% vs 33% for CD4+ cells). B cells, NK cells and monocytes were better conserved (except in GATA2 deficiency characterised by monocytopaenia). Genital oedema and likelihood of concomitant intestinal lymphangiectasia independently predicted CD4+ T cell depletion. Analysing CD4+ and CD8+ T cells by differentiation markers revealed disproportionate depletion of naïve cells, with a skewing towards a more differentiated effector profile. Systemic PLA conditions were associated with: increased expression of Ki67, indicative of recent cell division, in naïve CD4+, but not CD8+ T cells; increased levels of activation in CD4+, but not CD8+ T-cells; and an increased proportion of Treg. Skin-homing marker (CCR10, CLA and CCR4) expression was reduced in some patients with simplex phenotypes. Discussion Patients with PLA who have dysfunctional lymphatics have a selective reduction in circulating lymphocytes which preferentially depletes naïve CD4+ T-cells. The presence of systemic disease, genital oedema, and intestinal lymphangiectasia independently predict CD4 lymphopaenia. The association of this depletion with immune activation and increased circulating Tregs suggests lymphatic-lymphocyte interactions and local inflammatory changes are pivotal in driving immunopathology.